Prevalence and Incidence of Desquamative Gingivitis among Patients Visiting a Private Teaching Hospital in Chennai, India - A.Shamaa Anjum1 , Pratiba Ramani2 , Delphine Priscilla Antony S3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Desquamative gingivitis (DG) is a term indicating epithelial desquamation, erythema, erosion and/orvesiculobullous lesion of the attached and marginal gingiva. The lesions of DG mainly involve the buccalaspect of the gingiva. The term desquamative gingivitis is not a specific diagnosis , but describe severalmucocutaneous disorders major of which are oral lichen planus (OLP), mucous membrane pemphigoid(MMP), pemphigus vulgaris (PV). The aim of the study was to assess the prevalence and incidence ofdesquamative gingivitis among the patients visiting the outpatient department of periodontics at a privateteaching hospital , Chennai, India. This is a descriptive study which was performed under a universitysetting in which the data of patients who were diagnosed with desquamative gingivitis in the departmentof Periodontics at a private teaching hospital, Chennai from June 2019 to March 2020 was collected byreviewing patients records and the analysis of data of 86000 patients was done. The collected data wascompiled , reviewed, tabulated and imported to SPSS software (version 22.0) for statistical analysis. Theprevalence of desquamative gingivitis was found to be less 0.1% and had a female predilection (67%) andpatients between 50 to 60 years of age were more commonly affected by DG. Most cases of DG presentedwith burning sensation in the mandibular gingiva (50%) . The most common treatment of DG was foundto be pharmacotherapy mainly corticosteroids (50%) . Thus the knowledge of prevalence of desquamativegingivitis and correlation with various parameters is essential in dental practice for clinical implementation.